Divulgação científica e cidadania nas páginas da revista Minas Faz Ciência Infantil - Manoel de Oliveira Silva (2019)
The present study analyzed the scientific dissemination work carried out by the Minas Faz Children's Science Magazine, edited by the Foundation for Research Support in the State of Minas Gerais (FAPEMIG) and its contribution to the popularization of science in the State of Minas Gerais. For this the main objectives of the research were to identify the concept of science expressed in the editorials and in the topics addressed in the editions; the possibilities of building scientific citizenship from the scientific dissemination carried out by the journal; the media discourse as an instrument for translating scientific knowledge into the journal's public; the graphic and iconographic aspects, used as language resources for the compression of the topics covered. For the background of the research, the theoretical framework raised sought to take into account the concepts of scientific dissemination and popularization of science; information as a duty of the State and as a social right, the construction of citizenship through educational processes and the characteristics of media discourse. As an exploratory and descriptive research, the editions published in the months of December of the years of 2015, 2016 and 2017 were chosen as the corpus of the study, during which period the physical and electronic recording of reports were collected , editorials, interviews and photographs published by the magazine and which were constituted in the analyzed material. The data collected were organized and classified in a table, taking into account the topics covered, the titles and the number of reports per theme in each edition of the journal. From this survey and the classification, an analysis was carried out considering the previously established criteria, being the editorials first, followed by the reports. The analysis of the material demonstrated that the concept of science expressed by the magazine Minas Faz Children's Science goes through the understanding that science is an activity that is present in people's daily life and confirmed the hypothesis raised by the research project that the work of dissemination in the three editions published so far, contributes to the popularization of science. The approach and use of textual and graphic resources with the aim of facilitating the understanding of the topics treated in the reports bring the reader closer to the universe of science and opens possibilities for the realization of a citizen science where the reader can become an agent that contributes to the development of science itself.